Profesionalisme Guru SKI DI MIN 3 Labuhan Batu Selatan - Abdul Gani Jamora Nasution; Khoirul Bariah Rambe; Nur Aisyah Dalimunthe; Nurul Fatwa Sipayung; Ririn Indriani (Universitas Muhammadiyah Enrekang, 2022)
The history of Islamic culture is one of the subjects in the madrasa curriculum, studying SKI cannot be separated from the teacher's role, therefore the SKI teacher must be professional in managing classes, researchers examine related issues, How do teachers plan SKI learning, How do teachers implement SKI learning , And what about teacher professionalism in learning SKI, using descriptive qualitative research methods, through interviews and observations, with primary data sources SKI teachers and secondary data sources Principals as well as students at MIN 3 Labuhan Batu Selatan. It can be concluded that learning planning uses RPP through RPP design, method selection, media selection, and also selection of evaluation methods, implementation of learning using learning videos that are displayed on LCD projectors, Teacher professionalism is very important within the scope. It is found that teacher professionalism at MIN 3 Labusel is increasing by attending Diklat and KKG.the researcher states that the SKI teacher at MIN 3 Labuhan Batu Selatan is quite professional .